Visual Media as Assisting Instrument to Improve Students' Listening Ability - Wardaya, Marina (Universitas Ciputra, 2018)
Visual media is not merely for designers or visual communication design department, but also as the way to use visual media for teaching. Teaching by lecturing method frequently made students to become simply bored and did not pay attention and consequently did not graduate from college. It is believed that through visual media will help students to pay attention to the lessons and be enthusiastic in learning. The purpose of this study is to find out how visual media as Assisting Instrument to Improve Students’ Listening Ability. It is expected that this research can be useful for educators or lecturers to improve the quality of teaching and be able to improve students' ability to pay attention.